Probing electrical conduction behavior of BaSnO3 - Upadhyay S.; Sahu A.K.; Kumar D.; Parkash O. (My University, 2025)
The ac conductivity, σac of BaSnO3 has been measured in the temperature range 310-520 K and frequency range 100 Hz-1 MHz. Below 420 K the conductivity is almost independent of temperature while between 420 and 520 K it is temperature dependent. At 100 kHz the activation energy of these two regions is 0.08 and 0.35 eV, respectively. It has been proposed that in the low temperature region conduction is due to hopping of charge carriers among the Sn+2 and Sn+4 sites. In the high temperature region conduction is due to excitation of charge carriers at the edges of the conduction band and hopping at energies close to it. Further impedance and modulus spectroscopy studies show that the conduction mechanism is the same for grains and grain boundaries. © 1998 American Institute of Physics.